2019
DOI: 10.1093/infdis/jiz252
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biomarkers of Human Immunodeficiency Virus–Related Systemic Inflammation and Immune Activation in Sub-Saharan Africa Before and During Suppressive Antiretroviral Therapy

Abstract: We evaluated immune biomarker profiles in human immunodeficiency virus (HIV)–infected adults (n = 398) from 5 African countries. Although all biomarkers decreased after antiretroviral therapy (ART) initiation, levels of C-X-C chemokine ligand 10 (CXCL10), lipopolysaccharide-binding protein, C-reactive protein, soluble CD163, and soluble scavenger receptor CD14 were significantly higher during ART than in an HIV-uninfected reference group (n = 90), indicating persistent monocyte/macrophage activation, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 13 publications
5
27
1
Order By: Relevance
“…Contradictory results have been reported from different studies on the effect of cART on sCD14 (3335) due to a variety of contributors (36, 37). On the other hand, sCD163, a marker of vascular inflammation (38) and neurocognitive impairment (39), was higher in PLHIV than in healthy controls, which is in contrast to previous reports (40) but in line with other studies which showed that sCD163 was higher compared to the HIV-negative controls within 2 years of therapy (41, 42). The novelty of our study was to explore a large panel of inflammatory markers and we showed significantly higher levels of MMP1 (43), ADA (44), CD8A (16), SLAMF1 (45), and CCL23 (46) in PLHIV on long term ART.…”
Section: Discussionsupporting
confidence: 66%
“…Contradictory results have been reported from different studies on the effect of cART on sCD14 (3335) due to a variety of contributors (36, 37). On the other hand, sCD163, a marker of vascular inflammation (38) and neurocognitive impairment (39), was higher in PLHIV than in healthy controls, which is in contrast to previous reports (40) but in line with other studies which showed that sCD163 was higher compared to the HIV-negative controls within 2 years of therapy (41, 42). The novelty of our study was to explore a large panel of inflammatory markers and we showed significantly higher levels of MMP1 (43), ADA (44), CD8A (16), SLAMF1 (45), and CCL23 (46) in PLHIV on long term ART.…”
Section: Discussionsupporting
confidence: 66%
“…In acute HIV-1 infection the viral load rapidly increases alongside a burst of cytokines such as IFN-α and overstimulated pro-apoptotic CD4+ T cells; the immunological hallmark of HIV-1 infection (157). There is mounting evidence that chronic HIV-1 disease progression is characterized by systemic immune activation and oxidative stress, which can occur even while viremia is controlled with antiretrovirals (158)(159)(160). This systemic inflammation is thought to be caused by a number of factors; namely gut permeability, activated monocytes and cytokine derangement (160)(161)(162)(163).…”
Section: Conditions Associated With Tb Reactivation: Hiv-1 Infection mentioning
confidence: 99%
“…There is mounting evidence that chronic HIV-1 disease progression is characterized by systemic immune activation and oxidative stress, which can occur even while viremia is controlled with antiretrovirals (158)(159)(160). This systemic inflammation is thought to be caused by a number of factors; namely gut permeability, activated monocytes and cytokine derangement (160)(161)(162)(163). High levels of viremia are accompanied by high levels of IFN-γ, TNF-α, IFNα, and other inflammatory markers (164)(165)(166).…”
Section: Conditions Associated With Tb Reactivation: Hiv-1 Infection mentioning
confidence: 99%
“…During HIV-1 infection, persistent immune activation and inflammation are driven by multiple factors, including residual virus replication, inflammatory lipids, gut microbial translocation, and coinfection [92][93][94]. Although long-term effective ART substantially reduces the level of immune activation and inflammation in HIV-1-infected individuals, it fails to normalize the activation and inflammation [95][96][97][98][99]. It was reported that persistent T-cell activation was associated with decreased CD4 + T-cell gains in HIV-1-infected individuals during ART 53.…”
mentioning
confidence: 99%